Increased productivity of the Red Pitaya (Hylocereus undatus) byartificial lighting with renewable energy - Fernández Argüelles, Lorenzo Ricardo; Chediak Silva, Juliett; Sánchez Companioni, Roberto (Revista Universidad de Guayaquil, 2015)
Currently is vital the role of universities in promoting regional and economic development. Universities act celerate innovation and entrepreneurship through the transfer of knowledge. Since the early eighties of last century, process management has been widely used by universities and organizations employing Systems of Quality Management. This approach shows a systemic vision of the key processes that allow responding to the needs of society. The purpose of this paper is to model the process of knowledge transfer at the University of Guayaquil. This modeling is performed based on a process approach. The main theoretical methods include the analysis and synthesis of information obtained Inductive - deductive and systemic structural. The empirical methods are related to psychosocial information search tools and process mod deling, the study of potential markets for products or services derived from processes of entrepreneurship and innovation in the University.
Keywords: Red Pitahaya; productivity; renewable energy; light energy; antioxidant; pH; Brix degrees (Bx)